THE KITCHEN LIBRARY : VEGETARIAN COOKING - Handslip, Carole, author 334453 (London : Octopus Books, 1986)
Designed for both the amateur and the more experienced cook, this book is one of a range of paperbacks which form a complete cookery library. A selection of vegetarian recipes, including soups, starters, salads, main-course egg, cheese and vegetable dishes and a selection of dishes based on beans, pulses and nuts are included as well as a range of recipes for puddings, breads and cakes. Advice on planning vegetarian meals and nutritional information is also featured.